(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Fermentation-based bioenergy production is gaining popularity owing to its ease of use and broad range of feedstock options. Anaerobic fermentation of biological waste resources is widely regarded as a cost-effective and well-proven technique that allows for waste management and energy generation at the same time. In the developing world, The use of small-scale biogas plants to change waste into gas by aerobic digestion of organic materials is becoming more common. Biogas produced in small-scale biogas systems is of poor grade, was assessed in this study since it has a direct impact on its usage (as a fuel for biogas cookers) and may affect the choice to purchase such equipment. At 107 small-scale biogas facilities, the composition of biogas was tested using a multifunctional portable gas analyser. A questionnaire survey of biogas plant owners (n = 107) was used to gather additional data at the home level. The average daily biogas output is 0.499 m3, which is insufficient to meet the needs of rural families that rely on other sources of energy. In terms of biogas arrangement, biogas plants earlier than five years had a mean content of 65.44 percent methane (CH4) and 29.31 percent carbon dioxide (CO2), whereas biogas plants elder than 5 years had a mean content of 64.57 percent CH4 and 29.93 percent CO2.